2017
DOI: 10.4028/www.scientific.net/kem.739.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variation of Gap Thickness of the Thrust Bearing on Gap Pressure and Stiffness of the Aerostatic Spindle in Vertical Milling

Abstract: When the partially porous aerostatic thrust bearing and the journal bearings of an aerostatic spindle in a vertical milling machine are subjected to cutting load and gravitational force, the thicknesses of gaps between the thrust plate and the spindle flange will change. This study applied CFD software to analyze the effect of variations of gap thickness and rotating speed on the pressure in the gaps of the bearings and the stiffness of the spindle. The results revealed that, when the thrust plate and the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was found that pressure was significantly influenced by the film's thickness. Increasing spindle speed could lead to higher pressure on the spindle surface and increased spindle stiffness [34]. Zheng et al investigated the hydrodynamic hammering phenomenon and performance of a concave-hole single-tile bearing.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that pressure was significantly influenced by the film's thickness. Increasing spindle speed could lead to higher pressure on the spindle surface and increased spindle stiffness [34]. Zheng et al investigated the hydrodynamic hammering phenomenon and performance of a concave-hole single-tile bearing.…”
Section: Introductionmentioning
confidence: 99%